Penyuluhan Anti Bullying Guna Meningkatkan Pembangunan Pendidikan Karakter Siswa di SMK Armaniyah Cikarang - Sarwo Edy; Listian Indriyani Achmad; MH Ainulyaqien; Siti Juariah; Nenda (DPPM Universitas Pelita Bangsa, 2021)
Based on a report from Media Indonesia, the level of violence against children in West Java Province is still high. Last year, around 1,088 children were victims of violence. One case in point is the bullying of an eleven-year-old boy in Tasikmalaya Regency, West Java, which was highlighted among various cases of violence against children this year. The programme includes presenters who deliver training materials using various methods, such as lectures, questions and answers, discussions, demonstrations and tutorials with qualitative observation methods. Many factors can influence bullying behaviour in the home environment. Some of them are parents who often punish their children, stressful, aggressive and hostile situations in the family, family disharmony, parenting that causes children to express negative emotions outside, and family rules that are too strict and built without encouragement and child protection is carried out through various parties, including the government, family, school, and community. information about the types of bullying that are common in children and adolescents is very important for parents, teachers, and the community to know and be free from bullying behaviour. information about the types of bullying that are common in children and adolescents is very important for parents, teachers, and the community to know. By understanding these types of bullying behaviour, they can more easily identify if their children are victims or perpetrators of bullying. Related parties also need to continue to coordinate and collaborate in implementing bullying prevention programs in order to create a school and community environment that is safe, comfortable, and free from bullying behaviour.